Thermal comfort studies in non-conditioned room / Fauzan Shaile Elias - Elias, Fauzan Shaile (2002)
In order to achieve Thermal Comfort, there are several factors and parameters that need to be studied and understood. In doing this research, the parameters involve are temperature, relative humidity and air speed. Thermal design must, therefore, be closely concerned with comfort. This means that the building design and installations must be capable of achieving the necessary balance of environmental factors to give thermal comfort. To give thermal comfort a building interior must provide environmental conditions, which enable the bodies of occupants to lose heat at the rates and by means, which maintain comfort and also provide a less definable quality, ‘freshness’. The research of Thermal comfort study needs to be done continuously. This because the outdoor climate that always changing time to time depend on the weather and environment. Therefore the studies need to be done continuously in order to get the optimum comfort zone. To make this research better, the latest and accurate equipment need to be used in taking the data. For only with appreciation and support from many parties in continuing this research will there be the best comfort zone ever.